Global Urban Carbon Networks: Linking Inventory to Modeling - Chen, Shaoqing; Long, Huihui; Fath, Brian D; Chen, Bin (Environmental science & technology, 2020)
Cities utilize and manipulate an immense amount of global carbon flows through their economic and technical activities. Here, we establish the carbon networks of eight global cities by tracking the carbon exchanges between various natural and economic components. The metabolic properties of these carbon networks are compared by combining flow-based and interpretative network metrics. We further assess the relations of these carbon metabolic properties of cities with their socioeconomic attributes that are deemed important in urban development and planning. We find that, although there is a large difference in city-level carbon balance and flow pattern, a similarity in intercomponent relationships and metabolic characteristicsdoes exist. Cities with lower per capita carbon emissions tend to have healthier metabolic systems with more cooperative resource allocation among various industries, which indicates that there may be synergy between urban decarbonization and carbon-containing resource system optimization. A combination of indicators from flow balance and network models is a promising scheme for linking sector-based carbon inventories to system-based simulations of carbon management efforts. With this done, we may be able to reduce the knowledge gap with respect to how various carbon flows in cities can be concertedly managed considering both the restraint from their climate mitigation goals as well as the impact on urban social and economic development.
Keywords: velkoměsta; Economic Development; Cities; obnova měst; uhlík; Carbon; Carbon Dioxide; Urban Renewal; oxid uhličitý; ekonomický rozvoj